Influence of the Positive Electrode on Li4Ti5O12 (LTO) Electrode/Electrolyte Interfaces in Li-Ion Batteries. Issue 13 (15th September 2018) - Gauthier, Nicolas; Courrèges, Cécile; Goubault, Lionel; Demeaux, Julien; Tessier, Cécile; Martinez, Hervé
Abstract : Li4 Ti5 O12 (LTO)-based negative electrode for lithium-ion batteries is of interest for electrical vehicles due to its safety, low cost and cycling stability. In this study, the effect of the positive electrode on the electrochemical performances of LTO electrodes, in relation with the Solid Electrolyte Interphase (SEI) properties, has been investigated. Full cells LTO/LiNi3/5 Co1/5 Mn1/5 O2 (NMC) and LTO/LiMn2 O4 (LMO) were cycled at 40°C over 100 cycles and the electrodes were analyzed by XPS and Scanning Auger Microscopy (SAM) after one and 100 cycles. For both systems, LTO electrodes are homogeneously covered by surface layers since the first cycle which induces an irreversible capacity loss. This latter is more important for LTO/LMO compared to LTO/NMC. Both SEI layers are composed of organic (polyethylene oxides, oxalates) and inorganic species (LiF, phosphates and fluorophosphates) but in different proportions: more fluorine species are detected for LTO/LMO for instance. Moreover, the SEI is thicker on the LTO electrode when cycled versus LMO compared to NMC and contains small amounts of manganese, homogeneously spread over the surface. In conclusion, a thick SEI associated with the presence of metallic species could alter the passivating role of the SEI and explain the less efficient electrochemical performance of LTO/LMO cells.